Common Molecular Alterations in Canine Oligodendroglioma and Human Malignant Gliomas and Potential Novel Therapeutic Targets - Mitchell, Dana; Chintala, Sreenivasulu; Fetcko, Kaleigh; Henriquez, Mario; Tewari, Brij N.; Ahmed, Atique; Bentley, R. Timothy; Dey, Mahua (Frontiers in Oncology, 2019)
Spontaneous canine (Canis lupus) malignant glioma holds tremendous potential as an immunocompetent large animal model of human malignant gliomas (MG). However, the feasibility of utilizing this model in pre-clinical studies depends on a thorough understanding of the similarities and differences of the molecular pathways associated with MG between the two species. We have previously shown that canine MG has an immune landscape and expression pattern of commonly described oncogenes similar to that of human disease. In the current study, we performed a comprehensive analysis of canine MG RNAseq data to identify highly dysregulated genes in canine tumors. We then evaluated the expression of these genes in human MG using Xena Browser, a publicly available database. STRING-database inquiry was used in order to determine the suggested protein associations of these differentially expressed genes as well as the dysregulated pathways commonly enriched by the protein products of these genes in both canine and human MG. Our results revealed that 3,712 (23%) of the 15,895 differentially expressed genes demonstrated significant up- or downregulation (log2-fold change > 2.0). Of the 3,712 altered genes, ~50% were upregulated (n=1858) and ~50% were downregulated (n=1854). Most of these genes were also found to have altered expression in human MG. Protein association and pathway analysis revealed common pathways enriched by members of the up- and downregulated gene categories in both species. In summary, we demonstrate that a similar pattern of gene dysregulation characterizes both human and canine MG and provide additional support for the use of the canine model in order to therapeutically targeting these common genes. The results of such therapeutic targeting in the canine model can serve to more accurately predict the efficacy of anti-glioma therapies in human patients.